Radiotherapy in the treatment of bone metastases - Badzio, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2001)
Bone is the most common site of cancer dissemination and 80% of patients in terminal phase of cancer have bone metastases. Seventy percent of patients with bone lesions present with pain requiring therapy. Radiotherapy plays major role in the treatment of painful bone metastases. Another goal of irradiation may be recalcification of osteolytic lesions. Radiotherapy provides effective palliation in around 80% of patients. The average time to the occurrence of pain relief is two weeks and the mean duration of analgesic effect is around 30 weeks. Randomized studies comparing single dose of 8 Gy versus fractionated regimes in radiotherapy of painful bone metastases showed no differences in efficacy between these two approaches. Irradiation may be indicated in case of spinal cord compression or may be used as an adjunct to surgical bone stabilization. Radiotherapy is an essential component of palliative management of bone metastases, and a single dose of 8 Gy is sufficient in the majority of patients.